ECB Debt Certificates — New Use for an Old Instrument? - Arne Hansen; Dirk Meyer (Wirtschaftsdienst)
Abstract In response to the coronavirus crisis, the central banks of the Eurosystem have further increased their APP bond purchases and supplemented them with purchases under the PEPP programme. Together with other unconventional monetary policy measures, this generated additional liquidity would have to be reduced in the case of sustained higher inflationary pressure. The straightforward solution for the ECB would be to sell the once purchased bonds, as they are the source of the extra liquidity. However, the associated writeoffs would result in financial sector instabilities and interest rate increases on government bonds, which would be particularly problematic for crisis-hit countries. This contribution analyses the issuance of debt certificates by the ECB as an alternative way of absorbing liquidity.